Electric field response of molecular reactivity descriptors: a case study - Kar, Rahul; Pal, Sourav (Theoretical Chemistry Accounts, 2008)
In the present article, we study the influence of external electric field on the density-based global and local reactivity descriptors using examples of some planar nonlinear polyatomic molecules with C-2V point group symmetry. The study mainly involves the application of weak electric field in a direction along the principal axis and along its perpendicular direction. We also discuss the strength of the electric field studied in this work in terms of the strength of the molecular interaction. The work is expected to throw light on the effect of interactions within the above range on reactivity descriptors. Results are presented for a few prototype molecules.
Keywords: electric field; molecular interaction; planar nonlinear polyatomic molecules; Reactivity descriptors

Effect of solvents having different dielectric constants on reactivity: a conceptual DFT approach - Kar, Rahul; Pal, Sourav (International Journal of Quantum Chemistry, 2010)
Conceptual density functional theory is exploited to understand the reactivity in a medium of solvents with increasing dielectric constants. Aprotic as well as protic solvents are used for this study. It is found that the global parameters, such as chemical potential and hardness, decrease from gas phase to solvent phase with increasing dielectric constant. However, it is observed that the Fukui functions of the reactive atoms increase significantly with the dielectric constants of the aprotic solvents while for the protic solvents the variation of the reactivity indices is insignificant. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 110: 1642-1647, 2010
Keywords: COSMO; DFT; dielectric constant; Reactivity descriptors; solvent effect